2006
DOI: 10.2495/st060071
|View full text |Cite
|
Sign up to set email alerts
|

Tourism as a factor of development

Abstract: If well exploited and closely linked with other sectors of the economy, tourism is believed to serve as an engine of growth. This paper shows how the tourism sector can be a factor of development by offering diverse job opportunities and by increasing foreign earnings which in many nations are used to boost other economic activities. Activities that are developed as a result of tourism include among others: entertainment, transportation services, craft rental and sales, tour guides, restaurants, hotels, beach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The contribution of Tourism sector to development needs to be clearly explained to allow countries to invest into tourism. Tourism is considered as a development factor [6] as is probably the best example among human activities in which the linkages between environmental quality and economic prospects are evident [7]. Tourism is a part of a general strategy towards sustainability there is little agreement on, or evidence of, how to achieve this.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of Tourism sector to development needs to be clearly explained to allow countries to invest into tourism. Tourism is considered as a development factor [6] as is probably the best example among human activities in which the linkages between environmental quality and economic prospects are evident [7]. Tourism is a part of a general strategy towards sustainability there is little agreement on, or evidence of, how to achieve this.…”
Section: Introductionmentioning
confidence: 99%
“…A large and growing body of literature has investigated tourism multiplier effect from a theoretical or empirical point of view during the last decades (Ntibanyurwa, 2006;van Leeuwen, Nijkamp and Rietveld, 2009;Pascariu and Tiganasu, 2014). The multiplier effect was mostly used for the determination of economic impact of visitor spending, by multiplying it with the number of tourists and the average spending per visitor (Stynes, 1999).…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…Additional studies proved that the multiplier effect can be positively influenced by the level of national or regional economic diversification (Muchapondwa and Stage, 2013), due to the chances of involving more sectors of economy, the level of infrastructure (Freeman and Sultan, 1997;Huse, Gustavsen and Almedal, 1998), the number of inhabitants (van Leeuwen, Nijkamp and Rietveld, 2009) or the typology of tourist attractions (for example van Leeuwen, Nijkamp and Rietveld, (2009) found that the coastal destinations where the sun is the main resource tend to have a larger multiplier effect, while the destinations based on cultural resources recorded the lowest values of multiplier effect). Hansen and Jensen (1996) suggested that a richer region dominated by 3+ stars hotels tends to express a higher multiplier effect than a poorer region dominated by 2 stars' hotels or camping, while Ntibanyurwa (2006) offered evidence for a higher multiplier effect on the regions with small businesses.…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…The purpose of this study is to examine the image of the Cycladic and Samos region islands by analysing the interactions between tourism and the environment by examining environmental indices [11]. The population of Cyclades is mainly concentrated in Syros (19,870) Naxos (18,988), Thira (13,960), Paros (12,853), Andros (1,009) Mykonos (9,320) Tinos (8,574), the other islands' population is under 4,000. Samos' population is 33.814 and Ikaria's 8,312.…”
Section: General Characteristicsmentioning
confidence: 99%
“…The contribution of tourism sector to development needs to be clearly explained to allow countries to invest in tourism. Tourism is considered as a development factor [8] as it is probably the best example among human activities in which the linkages between environmental quality and economic prospects are evident [9]. Tourism is a part of a general strategy towards sustainability.…”
Section: Introductionmentioning
confidence: 99%